The Impact of the Preliminary Announcement on the Abnormal Returns of the Companies Involved in Takeover Bids in the Portuguese Stock Market between 2000 and 2014 - Braga, João Paulo; Gomes, Luís M. Pereira (Copernican Journal of Finance & Accounting, 2016)
The comprehension of terms such as Takeover Bids is essential to understand the functioning of business combinations. This paper aims to analyze the impact of the preliminary announcement on the abnormal returns of the companies involved in takeover bids in the Portuguese stock market. This study used the methodologies of Ball and Brown (1968) and Beaver (1968). 100 Operations were identified between 2000 and 2014. The results of the 12 analyzed bids confirm that the target companies show positive abnormal returns, whilst the acquiring companies show negative abnormal returns and inferior in amplitude. They also confirm that, globally, the companies react strongly to the announcement and that they acquire higher abnormal earnings in the periods closest to the preliminary announcement.